1 | initial version |
In your code you define x
and y
and then redefine then, which may be confusing. Below I distinguish the two definitions and convert g
into h
by simply evaluating it at new variables:
F = GF(3).algebraic_closure()
Rxy.<x, y> = PolynomialRing(F, 2)
g = x*y
Rx.<xx> = PolynomialRing(F)
Fx = FractionField(Rx)
FxRy.<yy> = PolynomialRing(Fx)
h = g(xx,yy)
2 | No.2 Revision |
In your code you define x
and y
and then redefine then, re-define them in a new way, which may be confusing. Below I distinguish the two definitions and convert g
into h
by simply evaluating it at new variables:
F = GF(3).algebraic_closure()
Rxy.<x, y> = PolynomialRing(F, 2)
g = x*y
Rx.<xx> = PolynomialRing(F)
Fx = FractionField(Rx)
FxRy.<yy> = PolynomialRing(Fx)
h = g(xx,yy)
3 | No.3 Revision |
In your code you define x
and y
and then re-define them in a new way, which may be confusing. Below I distinguish the two variables definitions and convert g
into h
by simply evaluating it at new variables:
F = GF(3).algebraic_closure()
Rxy.<x, y> = PolynomialRing(F, 2)
g = x*y
Rx.<xx> = PolynomialRing(F)
Fx = FractionField(Rx)
FxRy.<yy> = PolynomialRing(Fx)
h = g(xx,yy)